2020
DOI: 10.1109/twc.2019.2951770
|View full text |Cite
|
Sign up to set email alerts
|

Utility-Aware Optimal Resource Allocation Protocol for UAV-Assisted Small Cells With Heterogeneous Coverage Demands

Abstract: In this paper, we consider a UAV-assisted smallcell having heterogeneous users with different data rate and coverage demands. Specifically, we propose a novel utility-aware resource-allocation protocol to maximize the utility of UAV by allowing it to simultaneously serve the highest possible number of heterogeneous users with available energy resources. In this regard, first we derive a closed-form expression for rate-coverage probability of a user considering Rician fading to incorporate the strong line of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 40 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…As Rayleigh fading model is only applicable to the cases when there is no LoS link from the transmitter to the receiver, and the air-to-ground (A2G) channels are often dominated by LoS links, more and more recent works started to investigate the performance of UAV-aided communications with Rician fading model, which comprises a deterministic LoS component with a random multipath component, and is suitable for characterizing A2G channels with less shadowing but non-negligible small-scale fading. In [19], the number of users that could be served by the UAV was maximized in Rician fading, under the constraint of users' minimum rate-coverage probability requirements. In [20], the outage probability of the UAV-aided data collection with WPT was minimized in Rician fading, where the fixed UAV's altitude was assumed.…”
Section: B Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…As Rayleigh fading model is only applicable to the cases when there is no LoS link from the transmitter to the receiver, and the air-to-ground (A2G) channels are often dominated by LoS links, more and more recent works started to investigate the performance of UAV-aided communications with Rician fading model, which comprises a deterministic LoS component with a random multipath component, and is suitable for characterizing A2G channels with less shadowing but non-negligible small-scale fading. In [19], the number of users that could be served by the UAV was maximized in Rician fading, under the constraint of users' minimum rate-coverage probability requirements. In [20], the outage probability of the UAV-aided data collection with WPT was minimized in Rician fading, where the fixed UAV's altitude was assumed.…”
Section: B Related Workmentioning
confidence: 99%
“…However, in aforementioned works, see e.g., [19]- [20], the Rician factor was assumed as a constant without considering the effect of elevation angle on the channel gain. As UAV's elevation angle has great impact on the A2G link quality, it has been reported that omitting the effect of the elevation angle on the Rician channel modeling causes the analyzing bias to practical scenarios [21]- [23].…”
Section: Motivation and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations